The Effect of Capsule-in-Capsule Combinations on In Vivo Disintegration in Human Volunteers: A Combined Imaging and Salivary Tracer Study - Adrian Rump; Franziska N. Weiss; Louisa Schulz; Marie-Luise Kromrey; Eberhard Scheuch; Mladen V. Tzvetkov; Tyler White; Shane Durkee; Kevin W. Judge; Vincent Jannin; Aouatef Bellamine; Werner Weitschies; et al. (Pharmaceutics, 2021)
Controlling the time point and site of the release of active ingredients within the gastrointestinal tract after administration of oral delivery systems is still a challenge. In this study, the effect of the combination of small capsules (size 3) and large capsules (size 00) on the disintegration site and time was investigated using magnetic resonance imaging (MRI) in combination with a salivary tracer technique. As capsule shells, Vcaps® HPMC capsules, Vcaps® Plus HPMC capsules, gelatin and DRcaps® designed release capsules were used. The three HPMC-based capsules (Vcaps®, Vcaps® Plus and DRcaps® capsules) were tested as single capsules; furthermore, seven DUOCAP® capsule-in-capsule combinations were tested in a 10-way crossover open-label study in six healthy volunteers. The capsules contained iron oxide and hibiscus tea powder as tracers for visualization in MRI, and two different caffeine species (natural caffeine and 13C3) to follow caffeine release and absorption as measured by salivary levels. Results showed that the timing and location of disintegration in the gastrointestinal tract can be measured and differed when using different combinations of capsule shells. Increased variability among the six subjects was observed in most of the capsule combinations. The lowest variability in gastrointestinal localization of disintegration was observed for the DUOCAP® capsule-in-capsule configuration using a DRcaps® designed release capsule within a DRcaps® designed release outer capsule. In this combination, the inner DRcaps® designed release capsule always opened reliably after reaching the ileum. Thus, this combination enables targeted delivery to the distal small intestine. Among the single capsules tested, Vcaps® Plus HPMC capsules showed the fastest and most consistent disintegration.